Diffraction, Reverberation, Residue: Carceral Control and Its Effects in Nicaragua. - Weegels, Julienne (Social Justice, 2023)
The article examines the multifaceted effects of authoritarian carceral control in Nicaragua, focusing on how state violence and political imprisonment extend beyond physical detention to impact bodies, social relations, and memories through processes conceptualized as diffraction, reverberation, and residue. Drawing on prison ethnography and research with political prisoners, their families, and activists, it highlights how carceral control diffracts by weaponizing social networks to expand repression, reverberates through the embodied trauma and ongoing psychological effects of penal excess, and leaves a persistent residue that can both immobilize and be mobilized for resistance. Set against the backdrop of Daniel Ortega’s increasingly autocratic regime and the 2018 mass protests, the article situates Nicaragua’s hybrid carceral system within broader authoritarian strategies that criminalize dissent and solidarity, while also emphasizing the contested and incomplete nature of such control. This conceptual framework offers insights into the embodied and social consequences of political incarceration and state repression relevant to studies of authoritarianism and carceral governance.